ANALISIS PENGEMBANGAN KOMPETENSI PEGAWAI PADA DINAS PENDIDIKAN DI KOTA MAKASSAR: ANALYSIS OF EMPLOYEE COMPETENCE DEVELOPMENT IN EDUCATION DEPARTMENT IN MAKASSAR CITY - Faisal, Muhammad (Jurnal Pallangga Praja (JPP), 2020)
This study aims to determine the development of employee competence including the development of skills, knowledge, and attitude of employees at the Department of Education Makassar. The research used qualitative decriptive approach with the research informant is Head of Department, Secretary, Head of Division, and Head of Sub Division of General and Personnel as well as employees at Education Department of Makassar City. Data were collected by interview, observation and documentation technique, then the data were analyzed by three stages: data reduction, data display and verification / drawing conclusion. The results of the study explain that the development of employee skills in the form of leadership, functional and technical training. The development of employee competence in terms of knowledge development can be seen from formal education, non formal education, the appropriateness of discipline, and work experience. The development of employee competence in terms of employee attitude development can be seen from the activities of independence, spiritual lecture, direction, sanction, and appreciation.